Polyarylene sulfide resin and preparation method thereof

By controlling the ζ value and structural parts during the polymerization process, combining the phase separation agent and the agitated Reynolds number control, the problem of coloring of the polyarylene sulfide resin during the melt forming process is solved, and molded products with high whiteness and high mechanical strength are achieved.

CN119823382APending Publication Date: 2025-04-15WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202510001232.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The coloring problem caused by the decomposition of low molecular weight polymers during the melt forming process of polyaryl sulfide resins is difficult to effectively solve in the prior art, and the addition of commonly used coloring agents and whitening agents will reduce mechanical strength and increase production costs.

Method used

By using a capillary rheometer to meet the conditions of 0.75≤ζ<1, a polyarylene sulfide resin with a specific structural part as a repeating unit, and by controlling the relationship between the addition amount of phase separator and the stirred Reynolds number, the proportion of low-molecular-weight polyarylene sulfide is reduced to avoid coloring from the source.

Benefits of technology

The Hunter whiteness of polyarylene sulfide molded products has been achieved by more than 40%, which improves the whiteness and mechanical strength of the product, reduces production costs, and effectively solves the coloring problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823382A_ABST
    Figure CN119823382A_ABST
Patent Text Reader

Abstract

The invention provides a polyarylene sulfide resin and a preparation method thereof, (1) zeta of the polyarylene sulfide resin measured by a capillary rheometer satisfies 0.75 < = zeta < 1, zeta is defined as a ratio of phi 2 (310 DEG C, 10 min, 1216 sec <-1 >) / phi 1 (310 DEG C, 5 min, 1216 sec <-1 >), and phi # imgabs0 # is a ternary function of temperature T, retention time t and shear rate # imgabs1 #; (2) a resin structure having a structural moiety represented by formula (1) as a repeating unit and a structure in which an aromatic ring and a sulfur atom are bonded as a repeating unit; in formula (1), R1 and R2 each independently represent a hydrogen atom, an alkyl group having 1-4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethyoxyl group. The polyarylene sulfide resin of the present invention has little discoloration during melt molding, and can obtain pellets and molded articles having high whiteness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyarylene sulfide resin and a preparation method thereof, which can reduce the coloring of the polyarylene sulfide resin caused by the decomposition of low molecular weight polymers during melt molding, and belongs to the technical field of polymer materials. Background Art

[0002] As an emerging high-performance thermoplastic resin material, polyarylene sulfide occupies an important position in the field of materials science due to its excellent high temperature resistance, corrosion resistance, balanced mechanical properties and outstanding dimensional stability. It is known as the world's sixth largest engineering plastic and is widely used in many fields such as the automotive industry, electronic appliances and environmental protection industry. These application fields have strong requirements for the excellent color tone of polyarylene sulfide resin.

[0003] Phillips Petroleum Company prepared polyarylene sulfide by polymerization reaction of p-dichlorobenzene (referred to as p-DCB) and sodium sulfide in polar aprotic solvent, and took the lead in realizing the industrialization and commercial production of polyarylene sulfide. However, the first generation of products faced the challenges of low molecular weight and low melt viscosity, and further cross-linking and curing were required to increase their molecular weight before they could meet the application requirements. However, after high-temperature treatment in the presence of oxygen, polyarylene sulfide has problems such as strong brown coloration and insufficient mechanical strength. In order to improve the quality of polyarylene sulfide products, subsequent research focused on improving the polymerization process, such as adding polymerization aids such as water (JP1988039926A), alkali metal halides (JP2007106784A), alkali metal carboxylates (US5342654A) and alkaline earth metal aromatic carboxylic acids (JP1989043169) to promote the formation of high molecular weight polyarylene sulfide. During the pelletizing process of the extruder, the linear polyarylene sulfide prepared by adding specific additives is susceptible to environmental factors such as oxygen, resulting in free radicals and peroxides, which are easily thermally induced to color (in the present invention, "coloring" refers to spontaneous coloring or discoloration, rather than intentional coloring by adding colorants), resulting in a darker color of the polyarylene sulfide molded product.

[0004] In the processing of polyarylene sulfide, in order to suppress its heat-induced coloration phenomenon, free radical chain inhibitors and peroxide decomposers are often used to prevent coloration during the heating process. However, after the addition of free radical chain inhibitors and peroxide decomposers, there are problems such as polyarylene sulfide melt crosslinking and the lack of obvious coloration inhibition effect. In addition, the whiteness of polyarylene sulfide is improved by adding a large amount of pigments, titanium dioxide (TiO2) and other whitening agents, but the color of the resulting product is still relatively dim, and the addition of pigments will significantly reduce the mechanical strength of polyarylene sulfide. Therefore, how to avoid the coloration of polyarylene sulfide during processing from the source is the fundamental solution to the problems of the prior art. Summary of the invention

[0005] Polyarylene sulfide is easily colored due to the low molecular weight polymer being heated during the extrusion granulation process. The existing manufacturing technology usually adds free radical chain inhibitors, peroxide decomposers and pigments during the processing to improve the color of the polyarylene sulfide molded products. However, these technologies face the problems of high production cost, limited anti-coloring effect and reduced mechanical strength of the polyarylene sulfide molded products. The purpose of the present invention is to provide a polyarylene sulfide resin, which reduces the coloring phenomenon of polyarylene sulfide during the processing from the source, and the Hunter whiteness of the molded products after granulation can reach more than 40%.

[0006] Another object of the present invention is to provide a method for preparing the polyarylene sulfide resin.

[0007] A polyarylene sulfide resin, the polyarylene sulfide resin having the following characteristics:

[0008] (1) The ζ measured by capillary rheometer satisfies 0.75≤ζ<1, and ζ is defined as Φ2(310℃, 10min, 1216sec -1 ) / Φ1(310℃、5min、1216sec -1 ), where is the temperature T, holding time t and shear rate The ternary function of ;

[0009] (2) a resin structure having a structural part represented by formula (1) as a repeating unit, that is, a structure formed by bonding an aromatic ring and a sulfur atom as a repeating unit;

[0010]

[0011] In formula (1), R 1 and R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group or an ethoxy group.

[0012] In the present invention, the polyarylene sulfide resin can obtain a color tone with a Hunter whiteness of 40% or more after granulation.

[0013] In the present invention, the molecular weight distribution of the polyarylene sulfide resin is less than 5.

[0014] In the present invention, R represented by formula (1) 1 and R 2 A hydrogen atom is preferred; the position to which the hydrogen atom is bonded is preferably the para-position structure shown in formula (2) and the meta-position structure shown in formula (3).

[0015]

[0016] Preferably, the polyarylene sulfide resin has not only the structural part represented by formula (1), but also one or more of the structural parts represented by the following formulae (4) to (8); the content of the structural parts represented by formulae (4) to (8) is 10 mol% or less, preferably 3 mol% or less, relative to the total molar number of other structural parts; the bonding method of the structural parts represented by formulae (4) to (8) is preferably random copolymerization or block copolymerization.

[0017]

[0018] The method for preparing the polyarylene sulfide resin of the present invention comprises the following steps:

[0019] (1) Dehydration stage: Over a certain period of time, the temperature of a mixture of an organic polar solvent, a sulfur source, water, and an optional alkali metal hydroxide is gradually increased to remove water from the system.

[0020] As a preferred embodiment, in step (1), the organic polar solvent is selected from N-alkyl pyrrolidone compounds, N-cycloalkyl pyrrolidone compounds, N,N-dialkyl imidazolidinone compounds, tetraalkyl urea compounds, and hexaalkyl phosphoric acid triamide compounds.

[0021] As a preferred embodiment, the N-alkyl pyrrolidone compound or N-cycloalkyl pyrrolidone compound is preferably N-methyl-2-pyrrolidone or N-cyclohexyl-2-pyrrolidone; the N,N-dialkyl imidazolidinone compound is preferably 1,3-dialkyl-2-imidazolidinone; the tetraalkyl urea compound is preferably tetramethyl urea; and the hexaalkyl phosphoric acid triamide compound is preferably hexamethyl phosphoric acid triamide.

[0022] The molar ratio of the organic polar solvent to the sulfur source in the dehydration stage is 0.2-4.0, preferably 0.5-3.

[0023] As a preferred embodiment, in step (1), the sulfur source is selected from lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, preferably sodium sulfide or sodium hydrosulfide.

[0024] As a preferred embodiment, in step (1), the alkali metal hydroxide is selected from sodium hydroxide, calcium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide; the molar ratio of the alkali metal hydroxide to the sulfur source is 0 to 2, preferably 0.01 to 1.5;

[0025] The molar ratio of water added in the dehydration stage to the sulfur source is 1-20, preferably 4-10.

[0026] As a preferred embodiment, in step (1), the terminal temperature of the dehydration stage is 120-260°C, preferably 180-220°C, the heating rate is 0.1-3.5°C / min, preferably 0.5-2.0°C / min, and the molar ratio of the residual water to the sulfur source at the end of the dehydration stage is 0.5-3.0, preferably 0.8-1.8.

[0027] (2) One-stage polymerization: after dehydration is completed, a mixture of a dihalogen aromatic compound and an organic polar solvent is added, the temperature is raised to a certain temperature, and a polymerization reaction is performed under a certain pressure to generate a reaction mixture containing a prepolymer.

[0028] As a preferred embodiment, in step (2), the dihalogen aromatic compound is o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, dichlorotoluene, dichlorobiphenyl, dichlorobenzoic acid, dichlorodiphenyl ether, dichlorodiphenyl sulfoxide, dichlorobenzophenone, preferably p-dichlorobenzene.

[0029] Preferably, the molar ratio of the dihalogen aromatic compound to the sulfur source is 0.5 to 2.0, preferably 0.9 to 1.1.

[0030] The molar ratio of the total amount of the organic polar solvent to the sulfur source in the polymerization stage is 1-6, preferably 2-5.

[0031] As a preferred mode, the polymerization temperature of step (2) is 180-260° C., preferably 200-240° C., the polymerization pressure is 0-2 MPa, preferably 0.2-0.8 MPa, the reaction time is 30-240 min, preferably 60-180 min; the conversion rate of the dihalogen aromatic compound is 50%-98%, preferably 60-95%;

[0032] (3) Two-stage polymerization: After the first-stage polymerization is completed, the temperature is continued to be raised to a certain temperature, and the generated prepolymer is further reacted under a certain pressure. When the conversion rate of the dihalogen aromatic compound is greater than 50%, a phase separation agent is added. Preferably, the amount of the phase separation agent added α is proportional to the stirring Reynolds number N. Re Satisfy N Re ≥3.35+296α-232α 2 +67.9α 3 , α is the molar ratio of the phase separation agent to the sulfur source.

[0033] As a preferred embodiment, the polymerization temperature of step (3) is 240-290° C., preferably 250-270° C.; the polymerization pressure is 0.2-3 MPa, preferably 0.5-2.5 MPa; the reaction time after adding the phase separation agent is 0-300 min, preferably 30-240 min; the conversion rate of the dihalogen aromatic compound is 60%-100%, preferably 80-99.5%.

[0034] In the two-stage polymerization, the polymerization system changes to a phase separation agent state in the presence of a phase separation agent. Phase separation polymerization is to continue the polymerization reaction in a state where the reaction system is phase-separated into a polymer-rich phase and a polymer-poor phase. By adding a phase separation agent, the polymerization reaction system (polymerization reaction mixture) is phase-separated into a polymer-rich phase (a phase mainly composed of molten polyarylene sulfide) and a polymer-poor phase (a phase mainly composed of an organic polar solvent).

[0035] As a preferred embodiment, the phase separation agent is selected from water, organic carboxylic acid metal salts (for example, lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, lithium benzoate, sodium benzoate, sodium phenylacetate, potassium p-toluene benzoate), organic sulfonic acid metal salts (for example, sodium p-toluenesulfonate, sodium dodecylbenzenesulfonate, calcium ligninsulfonate, barium petroleum sulfonate), metal halides (for example, lithium chloride, potassium chloride) and paraffin hydrocarbons (for example, n-octadecane, n-octacosane, n-dotriacontane); these phase separation agents can be used alone or in combination of two or more; the molar ratio of the phase separation agent to the sulfur source is 0.1 to 5, more preferably 0.2 to 3.

[0036] (4) Post-treatment stage: The polymerization mixture is cooled, the reaction slurry is centrifuged and then washed and dried, preferably washed and filtered with acetone, then washed and filtered with an acid solution, and finally washed three times with hot water.

[0037] As a preferred embodiment, in step (4), the acid is preferably hydrochloric acid, sulfuric acid, nitric acid, carbonic acid, acetic acid, oxalic acid, malic acid, citric acid, more preferably hydrochloric acid or acetic acid.

[0038] As a preferred method, the blades of the reaction vessel used are preferably paddle-type, propeller-type, turbine-type, frame-type and anchor-type stirring paddles, and more preferably anchor-type stirring paddles or any combination of the above stirring paddles; the blade diameter d of the stirring paddle blade is not less than 50% and not more than 90% of the inner diameter D of the reaction vessel for reaction.

[0039] When the polyarylene sulfide in the present invention satisfies 0.75≤ζ<1 as measured by a capillary rheometer, the product has excellent thermal stability, a narrow molecular weight distribution, and a small proportion of low molecular weight substances. Therefore, the Hunter whiteness of the polyarylene sulfide molded product after granulation is greater than 40%.

[0040] In order to obtain a polyarylene sulfide resin with a molecular weight of 0.75≤ζ<1, the present invention provides a preparation method thereof as a preferred method, which effectively increases the probability and reaction activity of the thiolate or thiol group at the end of the obtained polymer colliding with the residual halogenated aromatic hydrocarbon by controlling the relationship between the amount of phase separation agent added and the stirring Reynolds number, thereby reducing the proportion of low molecular weight polyarylene sulfide, thereby solving the problem of coloring of polyarylene sulfide during extrusion granulation from the root.

[0041] The positive effects of the present invention are:

[0042] The present invention provides a polyarylene sulfide resin, which can prevent the polyarylene sulfide resin from being colored during melt molding and can obtain particles and molded products with high whiteness. DETAILED DESCRIPTION

[0043] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0044] The analysis and evaluation methods involved in the embodiments or comparative examples are as follows:

[0045] (1) Weight average molecular weight

[0046] The weight average molecular weight (Mw) of the polymer was measured using a high temperature gel permeation chromatograph (GPC) SSC-7000 under the following conditions. The weight average molecular weight was calculated as a polystyrene-equivalent value.

[0047] Solvent: 1-Chloronaphthalene

[0048] Temperature: 210℃

[0049] Detector: UV detector (360nm)

[0050] Sample injection volume: 200 μl (concentration: 0.05 mass %)

[0051] Flow rate: 0.7ml / min

[0052] Standard polystyrene: 5 kinds of standard polystyrene of 616000, 113000, 26000, 8200 and 600.

[0053] (2) Polymerization yield

[0054] Assuming that all the sulfur source introduced into the reactor is converted into polyarylene sulfide, the mass of polyarylene sulfide at this time (theoretical amount) is set as a reference value, and the ratio of the mass of polyarylene sulfide actually recovered (the sieve-surface material collected by an 80-mesh sieve) to the reference value is calculated, which is defined as the polymerization yield (unit: wt.%).

[0055] (3) Stirring Reynolds number

[0056]

[0057] Where:

[0058] ρ---Density of the material during polymerization, measured by an online density meter, Kg / m 3 ;

[0059] N---Agitator speed, r / s;

[0060] D---blade diameter, m;

[0061] μ---Viscosity of the material during polymerization, obtained by online viscometer, Pa·s.

[0062] (4) Phase separation agent dosage

[0063]

[0064] Unit: molS

[0065] (5) Conversion rate of dihalogen aromatic compounds

[0066] The amount of dihalogen aromatic compounds remaining in the slurry after the polymerization was completed was determined by gas chromatography (Agilent 7890B), and the conversion rate of the dihalogen aromatic compounds was calculated based on the residual amount, the feed amount of the dihalogen aromatic compounds, and the feed amount of sodium hydrosulfide.

[0067] (6)ζ

[0068] About 20g of dry polymer was used to measure the melt viscosity Φ using Shimadzu capillary rheometer CFT-500EX / 100EX. The capillary rheometer used a 1mmφ×10mm flat die and the test temperature was set to 310°C. The polymer sample was introduced into the device and kept for 5 minutes at a shear rate of 1216sec. -1 Φ1 was measured at 1216 sec. after 10 min. -1 Measure Φ2 below, ζ=Φ2 / Φ1.

[0069] (7) Hunter Whiteness

[0070] The color tone of the resin was evaluated by Hunter whiteness measured using a colorimeter. The resin sample for Hunter whiteness measurement was prepared by the following method. That is, a twin-screw extruder with a nitrided steel cylinder was used to pelletize at a temperature of 300°C, the pellets were preheated at 325°C for 3 minutes under a nitrogen flow using a hot press, and then pressurized at 325°C for 1 minute to form a sheet, and the amorphous sheet of about 2 mm obtained by rapid cooling was used as a sample.

[0071] Example

[0072] The following examples are given to further explain the embodiments of the present invention. Of course, the present invention is not limited to the following examples, and the details can be adopted in various forms.

[0073] Example 1

[0074] 1. Dehydration stage:

[0075] In a 50L titanium reactor (the paddle of the reactor is an anchor paddle, and the outer diameter d of the stirring paddle is 80% of the inner diameter D of the reactor), 46% NaSH aqueous solution (6855.16g, 56.25mol NaSH), 50% NaOH aqueous solution (4275g, 53.44mol NaOH), NMP (9466g, 95.63mol), the molar ratio of NaOH / NaSH is 0.95, and when the stirring Reynolds number is 100, the temperature is raised to 180°C at a heating rate of 1.2°C / min, and 5248.9g of aqueous solution (water content 88.1%) is removed. At this time, the molar ratio of the residual water content H2O / NaSH in the system is 1.2. After dehydration, the material temperature is reduced to 150°C.

[0076] 2. One-stage aggregation:

[0077] p-Dichlorobenzene (8434.86 g, 57.38 mol) and NMP (9466 g, 95.63 mol) were pumped into the reactor, and the molar ratio of p-dichlorobenzene / NaSH was 1.02. When the stirring Reynolds number was 100, the temperature was raised to 230°C in 90 minutes, and the first stage polymerization was completed at 230°C for 3 hours. After the first stage polymerization, the conversion rate of p-dichlorobenzene was 88%, and the terminal pressure of the first stage polymerization was 0.78 MPa.

[0078] 3. Two-stage aggregation

[0079] After the first stage polymerization, the temperature was raised to 260° C. at a heating rate of 2.0° C. / min, the stirring Reynolds number was increased to 180, and a sodium acetate aqueous solution (sodium acetate 461.25 g, 5.625 mol; water 1518.75 g, 84.38 mol) was added to the reactor by a centrifugal pump. The molar ratio of the total water content H2O / NaSH in the system was 2.7. The first stage polymerization was completed at 260° C. for 3 hours. After the second stage polymerization, the conversion rate of p-dichlorobenzene was 99.3%, and the terminal pressure of the second stage polymerization was 1.93 MPa.

[0080] 4. Post-processing stage

[0081] After the polymerization, the material temperature was lowered to 120° C. over 1 hour. The product was sieved using a 80-mesh screen, the sieve was centrifuged, the filter cake was washed with acetone, filtered, and then washed with a hydrochloric acid solution, filtered, and washed with boiling water 4 times. The obtained granular polyarylene sulfide was dried at 120° C. for 8 hours.

[0082] Example 2

[0083] In the preparation method of Example 2, 50% NaOH aqueous solution (4500g, 56.25mol NaOH), NMP (9466g, 95.63mol) are added in the dehydration stage, the molar ratio of NaOH / NaSH is 1, the dihalogen aromatic compound is dichlorodiphenyl sulfoxide (16479.5g, 57.38mol), and the conversion rate of dichlorodiphenyl sulfoxide after the first stage polymerization is 83.5%. The temperature is raised to 260°C at a heating rate of 2.0°C / min, the stirring Reynolds number is increased to 520, and water (2835g of water, 157.5mol) is added to the reactor through a centrifugal pump. The molar ratio of the total water content H2O / NaSH in the system is 4, and the conversion rate of dichlorodiphenyl sulfoxide after the second stage polymerization is 98.3%. The other material types and amounts in Example 2 are the same as those in Example 1, and the other experimental operations in Example 2 are consistent with those in Example 1.

[0084] Example 3

[0085] In the preparation method of Example 3, 50% NaOH aqueous solution (4590g, 57.38mol NaOH) and NMP (9466g, 95.63mol) were added in the dehydration stage, the molar ratio of NaOH / NaSH was 1.02, the dihalogen aromatic compound was dichlorodiphenyl ether (11857.4g, 57.94mol), and the conversion rate of dichlorodiphenyl ether after the first stage polymerization was 81.5%. The temperature was raised to 260°C at a heating rate of 2.0°C / min, the stirring Reynolds number was increased to 220, and lithium chloride aqueous solution (lithium chloride 238.4g, 5.625mol; water 1923.8g, 106.88mol) was added to the reactor by a centrifugal pump, the total water content H2O / NaSH molar ratio in the system was 3.1, and the conversion rate of dichlorodiphenyl sulfoxide after the second stage polymerization was 98.3%. The types and amounts of other materials in Example 3 are the same as those in Example 1, and the other experimental operations in Example 3 are consistent with those in Example 1.

[0086] Example 4

[0087] In the preparation method of Example 4, the dihalogen aromatic compound is p-dichlorobenzene (11857.4 g, 57.94 mol), and the conversion rate of p-dichlorobenzene after the first stage polymerization is 91.5%. The temperature is raised to 260°C at a heating rate of 2.0°C / min, the stirring Reynolds number is increased to 145, and a sodium p-toluenesulfonate aqueous solution (sodium p-toluenesulfonate 1103.6 g, 5.625 mol; water 303.8 g, 16.875 mol) is added to the reactor through a centrifugal pump. The molar ratio of the total water content H2O / NaSH in the system is 1.5, and the conversion rate of p-dichlorobenzene after the second stage polymerization is 99.3%. The types and amounts of other materials in Example 4 are the same as those in Example 1, and the other experimental operations in Example 4 are consistent with those in Example 1.

[0088] Example 5

[0089] In the preparation method of Example 5, 50% NaOH aqueous solution (4725g, 59.06mol NaOH) and NMP (9466g, 95.63mol) are added in the dehydration stage, the molar ratio of NaOH / NaSH is 1.05, the dihalogen aromatic compound is dichlorobiphenyl (13170.4g, 59.06mol), and the conversion rate of dichlorobiphenyl after the first stage polymerization is 70.5%. The temperature is raised to 260°C at a heating rate of 2.0°C / min, the stirring Reynolds number is increased to 180, and n-octadecane (2290.5, 9mol) is added to the reactor through a centrifugal pump. The conversion rate of dichlorobiphenyl after the second stage polymerization is 97.3%. The other material types and amounts in Example 5 are the same as those in Example 1, and the other experimental operations in Example 5 are consistent with those in Example 1.

[0090] Comparative Example 1

[0091] In the preparation method of Comparative Example 1, during the second-stage polymerization, the temperature was raised to 260° C. at a heating rate of 2.0° C. / min, the stirring Reynolds number was adjusted to 134, and water (1822.5 g, 101.25 mol) was added to the reactor via a centrifugal pump. The types and amounts of other materials in Comparative Example 1 were the same as those in Example 1, and the other experimental operations in Comparative Example 1 were the same as those in Example 1.

[0092] Comparative Example 2

[0093] In the preparation method of Comparative Example 2, after the first-stage polymerization was carried out for 1 hour, the conversion rate of p-dichlorobenzene was 39.3%, the stirring Reynolds number was adjusted to 180, and sodium acetate aqueous solution (sodium acetate 461.25g, 5.625mol; water 1518.75g, 84.38mol) was added to the reactor through a centrifugal pump, and the molar ratio of the total water content H2O / NaSH in the system was 2.7. The types and amounts of other materials in Comparative Example 2 were the same as those in Example 1, and the other experimental operations in Comparative Example 2 were consistent with those in Example 1.

[0094] The test data of each embodiment and comparative example are shown in Table 1.

[0095] Table 1 Test data of embodiments and comparative examples

[0096]

[0097]

[0098] From the above data, it is found that by adding a phase separation agent when the conversion rate of dihalogen aromatic compounds is greater than 50%, and controlling the stirring Reynolds number and the amount of phase separation agent added, the polymerization system can fully react in a highly phase-separated state, thereby obtaining particles and molded products with high whiteness.

Claims

1. A polyarylene sulfide resin, characterized in that: (1) The ζ measured by capillary rheometer satisfies 0.75≤ζ<1, and ζ is defined as Φ2(310℃, 10min, 1216sec -1 ) / Φ1(310℃、5min、1216sec -1 ), where is the temperature T, holding time t and shear rate The ternary function of ; (2) a resin structure having a structural part represented by formula (1) as a repeating unit, that is, a structure formed by bonding an aromatic ring and a sulfur atom as a repeating unit; In formula (1), R 1 and R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group or an ethoxy group.

2. The polyarylene sulfide resin according to claim 1, characterized in that: The polyarylene sulfide resin can obtain a color tone with a Hunter whiteness of 40% or more after granulation.

3. The polyarylene sulfide resin according to claim 1 or 2, characterized in that: The molecular weight distribution of the polyarylene sulfide resin is less than 5.

4. The polyarylene sulfide resin according to any one of claims 1 to 3, characterized in that: R represented by formula (1) 1 and R 2 is a hydrogen atom; the position where the hydrogen atom is bonded is preferably the para-position structure shown in formula (2) and the meta-position structure shown in formula (3).

5. The polyarylene sulfide resin according to any one of claims 1 to 4, characterized in that: The polyarylene sulfide resin further has one or more of the structural parts represented by the following formulae (4) to (8); the content of the structural parts represented by the formulae (4) to (8) is 10 mol% or less, preferably 3 mol% or less, relative to the total molar number of other structural parts; the bonding method of the structural parts represented by the formulae (4) to (8) is preferably random copolymerization or block copolymerization; 6. The method for preparing a polyarylene sulfide resin according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) a dehydration stage, wherein the temperature of a mixture of an organic polar solvent, a sulfur source, water, and an optional alkali metal hydroxide is gradually increased to remove part of the water in the system; (2) a first-stage polymerization, wherein after dehydration is completed, a mixture of a dihalogen aromatic compound and an organic polar solvent is added, and the temperature is raised to react to form a reaction mixture containing a prepolymer; (3) Two-stage polymerization: After the first-stage polymerization is completed, the temperature is continued to be raised to allow the generated prepolymer to further react. When the conversion rate of the dihalogen aromatic compound is greater than 50%, a phase separation agent is added. Preferably, the amount of the phase separation agent added α is proportional to the stirring Reynolds number N. Re Satisfy N Re ≥3.35+296α-232α 2 +67.9α 3 , α is the molar ratio of the phase separation agent to the sulfur source; (4) Post-treatment stage: the polymerization mixture is cooled, the reaction slurry is centrifuged and then washed and dried, preferably using acetone for washing and filtration, then washing and filtration with an acid solution, and finally washing with hot water and drying.

7. The preparation method according to claim 6, characterized in that: The terminal temperature of the dehydration stage in step (1) is 120-260° C., preferably 180-220° C.; and / or the heating rate is 0.1-3.5° C. / min, preferably 0.5-2.0° C. / min; and / or the molar ratio of the residual water in the dehydration stage to the sulfur source is 0.5-3.0, preferably 0.8-1.

8.

8. The preparation method according to claim 6 or 7, characterized in that: The dihalogen aromatic compound in step (2) is o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, dichlorotoluene, dichlorobiphenyl, dichlorobenzoic acid, dichlorodiphenyl ether, dichlorodiphenyl sulfoxide, dichlorobenzophenone, preferably p-dichlorobenzene; and / or, the molar ratio of the dihalogen aromatic compound to the sulfur source is 0.5 to 2.0, preferably 0.9 to 1.

1.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The polymerization temperature of step (2) is 180-260° C., preferably 200-240° C.; and / or, the polymerization pressure is 0-2 MPa, preferably 0.2-0.8 MPa; and / or, the reaction time is 30-240 min, preferably 60-180 min; and / or, the conversion rate of the dihalogen aromatic compound is 50%-98%, preferably 60-95%.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The polymerization temperature of step (3) is 240-290° C., preferably 250-270° C.; and / or, the polymerization pressure is 0-3 MPa, preferably 0.5-2.5 MPa, and / or, the reaction time after adding the phase separation agent is 0-300 min, preferably 30-240 min; and / or, the conversion rate of the dihalogen aromatic compound is 60%-100%, preferably 80-99.5%.

11. The preparation method according to any one of claims 6 to 10, characterized in that: The phase separation agent in step (3) is selected from water, organic carboxylic acid metal salts (preferably, lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, lithium benzoate, sodium benzoate, sodium phenylacetate, potassium p-toluenesulfonate), organic sulfonic acid metal salts (preferably, sodium p-toluenesulfonate, sodium dodecylbenzenesulfonate, calcium ligninsulfonate, barium petroleum sulfonate), metal halides (preferably, lithium chloride, potassium chloride, sodium chloride), alcohols (preferably, ethylene glycol, xylitol) and paraffin hydrocarbons (preferably, n-octadecane, n-octacosane, n-dotriacontane); these phase separation agents can be used alone or in combination of two or more; the molar ratio of the phase separation agent to the sulfur source is 0.1 to 5, more preferably 0.2 to 3.

12. The preparation method according to any one of claims 6 to 11, characterized in that: The blades of the reaction vessel used are paddle-type, propeller-type, turbine-type, frame-type or anchor-type stirring blades, preferably anchor-type stirring blades or any combination of the above stirring blades; more preferably, the blade diameter d of the stirring blade is not less than 50% and not more than 90% of the inner diameter D of the reaction vessel for reaction.

Citation Information

Patent Citations

  • Production of polyarylene sulfide

    JP1988039926A

  • Preparation of omelet like hand-made one

    JP1989043169A

  • Method for recovering polyphenylene sulfide oligomer

    JP2007106784A

  • Surface roughening of resin molded articles for metallizing

    US5342654A

Cited By

  • Polyarylene sulfide as well as preparation method and application thereof

    CN120757779A